Electromagnetic interference shielding effectiveness of polypyrrole-silver nanocomposite films on silane-modified flexible sheet. (April 2022) - Benzaoui, Karim; Ales, Achour; Mekki, Ahmed; Zaoui, Abdelhalim; Bouaouina, Boudjemaa; Singh, Ajay; Mehelli, Oussama; Derradji, Mehdi
The conventional electromagnetic interference (EMI) shielding materials are being gradually replaced by a new generation of supported conducting polymer composites (CPC) films due to their many advantages. This work presents a contribution on the effects of silane surface–modified flexible polypyrrole-silver nanocomposite films on the electromagnetic interference shielding effectiveness (EMI-SE). Thus, the UV-polymerization was used to in-situ deposit the PPy-Ag on the biaxial oriented polyethylene terephthalate (BOPET) flexible substrates whose surfaces were treated by 3-aminopropyltrimethoxysilane (APTMS). X-ray Photoelectron Spectroscopy (XPS) analyzes confirmed the APTMS grafting procedure. Structural, morphological, thermal, and electrical characteristics of the prepared films were correlated to the effect of substrate surface treatment. Thereafter, EMI-SE measurements of the elaborated films were carried out as per ASTM D4935 standard for a wide frequency band extending from 50 MHz to 18 GHz. The obtained results confirmed that the APTMS-treated BOPET film exhibit higher EMI shielding performance and better electrical characteristics compared to the untreated film. In fact, a 32% enhancement of EMI-SE was noted for the treated films compared to the untreated ones. Overall, these results put forward the role played by the surface treatment in strengthening the position of flexible PPy-Ag supported films as high-performance materials in electronic devices and electromagnetic interference shielding applications.